Plate fixation of acromion fracture using a mesh plate. (June 2021) - Kurahashi, Shingo; Takeda, Shinsuke; Mitsuya, So; Makihara, Koichiro; Yamauchi, Ken-ichi
Abstract: In several cases of treatment of acromion fractures of the scapula, plate fixation provides more rigidity to the fractured area. However, no specific plates are available for the acromion because of high interindividual variation in the shape of the acromion. We report two cases of acromion fractures operated using a mesh plate (Depuy Synthes, West Chester, PA, USA), which acts as a versatile, low-profile implant, being cut according to the specific fracture pattern and anatomical fitting. Our positive experiences with using a mesh plate may help to establish it as the operative procedure of choice in cases of acromion fracture.